Organizational climate for innovation: A study in Vietnam (2017)
This paper is devoted to studying the organizational climate for innovation (OCI) within the context of Vietnam. In this regard, we started by reviewing the organizational capabilities which can have a greater influence in the OCI within the firm. As result of this review, we establish absorptive capacity (AC) as a primer capability in terms of enhancing innovation within companies. In this work, we test the relationship between OCI and AC. By doing so, we applied a survey to managers within Vietnamese companies. Our sample is composed of 48 Vietnamese employees (83% with manager position). The data analysis used the regression analysis as a technique to test the significance of the relationships between AC and OCI dimensions. The main finding in this research is that in order to foster innovation the most important factor is the support that companies can generate for the innovation. It means that the availability of resources or the supply of financing advantages are not as fundamental factors as the climate of the company to foster innovation. This study contributes to the extant AC literature by empirically testing the AC relationship with organizational climate.